Costs of isocyanate-related occupational diseases: A systematic review. Issue 7 (3rd July 2019) - Kreis, Kristine; Aumann-Suslin, Ines; Lüdeke, Andreas; Wegewitz, Uta; Zeidler, Jan; Graf von der Schulenburg, J.-Matthias
Abstract: Although isocyanates are increasingly used in manufacturing and workplace exposure to isocyanates is widely recognized as one of the most frequent causes for occupational lung and skin diseases, little is known about the economic burden on the affected individual and the society. This study provides an overview on costs of occupational diseases related to isocyanates. We performed a systematic literature search of studies in the electronic databases of the German Institute of Medical Documentation and Information, and the Canadian Centre for Occupational Health and Safety. We extracted the key characteristics of the studies and performed a study quality assessment. We identified eight studies on the costs of illness, of which five focused on occupational lung diseases and three on occupational skin diseases. Further, eight studies calculated loss of income/compensation payments. Out of the 16 identified articles, only two reported costs directly attributable to isocyanate-induced diseases (asthma). Studies were hardly comparable because they differed substantially in their methodological approaches. Moreover, the quality assessment of the studies revealed substantial limitations. While a wide range of isocyanate-related costs was identified, consequences of isocyanate-related occupational diseases were considerable in terms of societal costs and loss of income. In most studies, indirect costs were the main cost driver. There is a need for high-quality cost of illness studies on isocyanate-induced diseases stratified by degree of severity and sex. Such studies provide valuable information to develop preventive strategies and set priorities for measures to lower the burden of professional health risks.